2016
DOI: 10.1002/ca.22720
|View full text |Cite
|
Sign up to set email alerts
|

The gross anatomy of the renal sympathetic nerves revisited

Abstract: Catheter-based renal denervation techniques focus on reducing blood pressure in resistant hypertension. This procedure requires exact knowledge of the anatomical interrelation between the renal arteries and the targeted renal nervous plexus. The aim of this work was to build on classical anatomical studies and describe the gross anatomy and anatomical relationships of the renal arteries and nerve supply to the kidneys in a sample of human cadavers. Twelve human cadavers (six males and six females), age range 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 25 publications
(37 reference statements)
3
29
1
Order By: Relevance
“…The kidney receives a more abundant nerve supply than any other abdominal organ with the exception of the adrenal glands . The anatomy of renal sympathetic nerves in humans has been recently revisited, mostly confirming findings from previous anatomical studies . The renal plexus is composed of nerve fibres coming from the celiac ganglion, inferior and posterior renal ganglia, superior mesenteric ganglion and thoracic splanchnic nerves.…”
Section: Anatomy Of Renal Nervesmentioning
confidence: 53%
See 2 more Smart Citations
“…The kidney receives a more abundant nerve supply than any other abdominal organ with the exception of the adrenal glands . The anatomy of renal sympathetic nerves in humans has been recently revisited, mostly confirming findings from previous anatomical studies . The renal plexus is composed of nerve fibres coming from the celiac ganglion, inferior and posterior renal ganglia, superior mesenteric ganglion and thoracic splanchnic nerves.…”
Section: Anatomy Of Renal Nervesmentioning
confidence: 53%
“…The renal plexus fibres run over the superior and inferior surfaces of the renal artery toward the renal hilum where they continue in the same orientation following the division of the hilar artery. All along their course, the main superior and inferior fibres are connected by thin twigs that run over the anterior and posterior surfaces of the renal arteries . In case of arterial variation, if more than one hilar artery is present, some nerves may cross the faces of the main renal artery to the accessory arteries.…”
Section: Anatomy Of Renal Nervesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that innervation was more important in the medial and the distal part of the renal artery, where the number of sympathetic fibres is higher . Furthermore, contradictory results are found about the predominant repartition of the fibres around the artery in the different studies . Fibres are perhaps statistically less represented in the dorsal region, but this is important to remember they are disseminated all around the artery.…”
Section: Methodsmentioning
confidence: 95%
“…Importantly, anatomical and histological studies later demonstrated that nerves are closer to the lumen in the distal part of the renal arteries, and the renal artery divisions, where they are more readily reached by delivered energy . Recent studies have also shown that innervation was more important in the medial and the distal part of the renal artery, where the number of sympathetic fibres is higher .…”
Section: Methodsmentioning
confidence: 98%